Cost of an Integrated Care Program to Reduce ED Visits During Diabetic Prisoner Court Hearings. (July 2017) - Pauley, Tim; Matienzo, Joy; Ventura, Joseph; Barbita, Josie
Diabetic events occurring during court hearings previously required emergency medical services (EMS) transport to the emergency department (ED). A new process was implemented whereby the provincial court (PC) was notified by the detention center of diabetes status of prisoners scheduled for court later that day, enabling a community nursing services provider to provide on-site diabetes assessment and treatment at the PC. During the 13-month pre-implementation phase, there were 10 incidents of diabetic distress resulting in an ED visit at a total cost of 797.58/prisoner, including police service personnel, EMS, and ED staff/physician. During the 12.5-month postimplementation phase, insulin was administered on-site during 72 court dates at a cost of 161.93/prisoner. The new process for managing diabetic needs of prisoners during court dates resulted in a substantial cost savings in terms of police services and health care personnel and improved the immediacy and quality of care for prisoners.